Care burden among the caregivers of children with cancer attending tertiary hospital, Bharatpur - Uprety, Sunita; Kumari Subba, Hem (Journal of Chitwan Medical College, 2025)
Introduction: Caring for the child with cancer is associated with tremendous physical, psychological, social, and financial pressure upon the family. Early detection of burden of care among caregivers is preeminent in promoting their quality of life. The aim of this study was to identify care burden among the caregivers of children with cancer attending a tertiary hospital, Bharatpur. Method: A cross-sectional study was carried out among caregivers of children attending B. P. Koirala Memorial Cancer Hospital, Bharatpur, Nepal. Non-probability consecutive sampling technique was used to select the desired sample. Data were collected from 10 Aug to 05 Nov 2020 by an interview schedule using a standardised caregiver burden scale. Data were analysed by using descriptive and inferential (chi-square and correlation) tests. A p≤0.05 was considered statistically significant. Result: Out of 110 caregivers, 61(55.5%) had a moderate level of care burden. Mean score of care burden was 52.22±12.820. There was a statistically significant association between caregivers’ level of care burden with economic status (p=0.023), health problem of the caregivers (p=0.008) and duration of disease diagnosis (p=0.019). There was a statistically significant positive relationship between all domains of care burden. Conclusion: Caregivers had a moderate level of care burden. Numerous factors associated with care burden were found. Healthcare professionals should show concern towards reducing the burden among the caregivers and carry out educational programs that help them cope with their problems.